Kernel type-based entries are efficient to develop a core collection of maize (Zea mays L.) - Jae-Han Son; Seongmin Hong; Ji Won Kim; Jiyun Go; Junyong Choi; Sang-Bum Lee; Jun Young Ha; Young-Sam Go; Hwan-Hee Bae; Tae-Wook Jung; Gibum Yi (Applied Biological Chemistry)
Abstract A core collection, a minimized set of germplasm representing maximum genetic diversity, is useful for breeding and genetic studies. Developing a core collection is essential for efficient genetic analysis. However, the process is time-consuming and requires considerable effort. Based on previous population structures of maize we hypothesized that kernel types can be representative characteristics encompassing large phenotypic variations. Here we showed that kernel type based entries are useful for developing a core collection representing large genetic variation. Based on genome-wide association studies (GWAS) of yellow kernel color and six yield related phenotypes, we found that y1 gene is responsible determinant of yellow color kernel and several genes were revealed to be involved in the yield-related phenotypes. The core collection was powerful to resolve the corresponding genetic components for the phenotypes. These results suggest that kernel types should be considered to include large genetic variation for developing a core collection in maize. This information will be facilitated to develop a new maize core collection.